Intellectual Capital Framework For University Based On Lamemba Accreditation Instrument - Ihyaul Ulum; Driana Leniwati; Tri Wahyu Oktavendi; Aviani Widyastuti (Jurnal Reviu Akuntansi dan Keuangan, 2023)
Purpose: The purpose of this research is to construct an intellectual capital framework university (ICFU) based on the accreditation instrument of the LAMEMBA study programme (Lembaga Akreditasi Mandiri Ekonomi, Manajemen, Bisnis, Dan Akuntansi). Methodology/approach: The methods used in this research were focus group discussions (FGD) and in-depth interviews with a number of stakeholders in the implementation of the accreditation of LAMEMBA study programmes. Findings: This research successfully constructed an intellectual capital framework for universities (ICFU) based on the LAMEMBA accreditation instrument. Practical implications: This framework consists of three main components, namely human capital, structural capital, and relational capital with details of the number of each item are: human capital 35 items, structural capital 22 items, and relational capital 8 items.